Pengembalian saham sektor perbankan dalam isu inflasi dan suku bunga - Rombang, Delphinia Sidney; Sigandong, Akrilia Prety Sinta (Manajemen Bisnis dan Keuangan Korporat, 2023)
Information on changes in inflation and interest rates is one of the issues that tend to influence investment decisions in the Indonesian capital market. This study observes from 1 February 2023 to 30 April 2023 at 47 firms in the banking sector. This study finds that the performance of stock returns on risk from the banking sector as a whole has not reached an optimal level. Specifically, the evidence also shows that there is a tendency for returns to decline from February to April 2023 as the inflation rate declines. The findings of this study also imply that a decrease in returns also occurs at a fixed interest rate. In addition, this study also finds that even though there is a decrease in returns but the difference of the value between periods are insignificant.